Language rights and legal identity: a sociolinguistic study of indigenous language representation in Indonesian law - Putri Lu'lua Faiza Dwany (Indonesian Journal of Linguistics and Legal Discourse, 2026)
Background: Indonesia is one of the world’s most linguistically diverse nations, yet indigenous languages remain marginalized in legal frameworks that privilege Bahasa Indonesia as the sole language of governance. Objective: The aim of this research is to examine how Indonesian law represents, protects, or silences indigenous languages in constructing legal identity. Method: Using a qualitative design, this study employed sociolinguistic textual analysis, critical language policy analysis, and ideological discourse analysis on constitutional provisions, statutory laws, regional bylaws, and judicial decisions. Results: The results show three main findings: first, indigenous languages are inconsistently represented in national legal texts, with recognition largely symbolic and confined to cultural or educational domains; second, there are significant policy gaps, as constitutional guarantees of cultural rights lack enforcement mechanisms and regional protections remain fragmented; third, legal discourse reflects an ideology of centralism that elevates Bahasa Indonesia while relegating local languages to folklorized or peripheral roles. Implication: These findings imply that without systemic integration, indigenous languages risk symbolic survival but functional exclusion, underscoring the need for inclusive legal reforms that embed linguistic rights into governance and justice. Novelty: This study exposes how Indonesian legal discourse simultaneously recognizes and marginalizes indigenous languages, revealing a tension between symbolic acknowledgment and their exclusion from functional domains of governance.